Highlights of soil and water conservation investments in four regions of Ethiopia - Adimassu, Zenebe; Langan, Simon J.; Barron, Jennie (International Water Management Institute, 2018)
This paper provides details of soil and water conservation (SWC) investments in Ethiopia over the past 20 years. It presents SWC practices and estimates the level of SWC investments in different regions. The paper focuses on four principal agricultural regions: Amhara, Oromia, SNNPR and Tigray. Primary and secondary data were collected for the analysis, and consultations were conducted at regional levels. Primary data on diverse SWC practices, their numbers and areal extent were obtained from the archives of regional Bureaus of Agriculture (BoAs). The results of this study show that several projects involving significant financial investment have been implemented to reverse land degradation and improve land productivity in Ethiopia since the 1970s. The list of projects is not comprehensive due to a lack of documentation at all levels, but it does provide some insights into the scale of SWC investments and implementation. The projects analyzed in the four regions fall into the following categories: farmland management, hillside management and gully rehabilitation practices, including check dams and cut-off drains. The analysis shows that these practices involved both paid and unpaid labor, together representing an estimated investment of more than ETB 25 billion (or approximately USD 1.2 billion) per year over the past 10 years. It is clear that large investments have been made in SWC activities in Ethiopia. However, the outcomes in terms of impact on yield and livelihood benefits are yet to be fully understood. A comprehensive assessment is needed to measure the impact of SWC activities on farmers’ livelihoods and the environment. A key recommendation arising from the analysis is that more data and information are needed on the successes and failures of SWC practices, which will assist stakeholders to better guide and target future projects and investments. An additional recommendation is to consider the biophysical and financial impact of soil erosion, both on and off farm.